2021
DOI: 10.3389/fpsyt.2021.633523
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Related Stressors and Chinese Adolescents' Adjustment: The Moderating Role of Coping and Online Learning Satisfaction

Abstract: The present study aims to examine the main and interactive relations of COVID-19-related stressors, coping, and online learning satisfaction with Chinese adolescents' adjustment during the COVID-19 pandemic. A total of 850 adolescents from three Chinese secondary schools participated in the survey during the pandemic outbreak, and the data were analyzed by hierarchical linear regression. The results show that COVID-19-related stressors were a vulnerability factor in predicting adjustment. Adolescents' adjustme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 24 publications
1
30
0
1
Order By: Relevance
“…The COVID-19 pandemic was an acute, large-scale, and uncontrollable stressor that may have taxed adolescents’ coping resources and exacerbated mental health concerns, including DSH ( Ammerman et al., 2021 ; Carosella et al., 2021 ; Cost et al., 2021 ; Craig et al., 2021 ; Hamza et al., 2020 ; Li et al., 2021 ; Singh et al., 2020 ). Accordingly, the pandemic provided a unique opportunity to test etiological models that propose central roles for stress and ER difficulties in the development of DSH (e.g., Chapman et al., 2006 ; Linehan, 1993 ; Nock, 2009 ; Van Heeringen, 2012 ; Williams, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic was an acute, large-scale, and uncontrollable stressor that may have taxed adolescents’ coping resources and exacerbated mental health concerns, including DSH ( Ammerman et al., 2021 ; Carosella et al., 2021 ; Cost et al., 2021 ; Craig et al., 2021 ; Hamza et al., 2020 ; Li et al., 2021 ; Singh et al., 2020 ). Accordingly, the pandemic provided a unique opportunity to test etiological models that propose central roles for stress and ER difficulties in the development of DSH (e.g., Chapman et al., 2006 ; Linehan, 1993 ; Nock, 2009 ; Van Heeringen, 2012 ; Williams, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to extensive disruptions to social and personal care routines, the pandemic engendered fear of infection, concerns with the health of family and friends, and worry of overloading the healthcare system ( Craig et al., 2021 ; Ellis et al., 2020 ; Styck et al., 2020 ). These COVID-19-related stressors may have taxed adolescents’ coping resources and elevated their risk of mental health difficulties, including anxiety, depression, post-traumatic stress, and deliberate self-harm (DSH; Ammerman et al., 2021 ; Carosella et al., 2021 ; Craig et al., 2021 ; Cost et al., 2021 ; Hamza et al., 2020 ; Li et al., 2021 ; Singh et al., 2020 ). DSH refers to intentional, self-inflicted, and non-fatal harm to one's body irrespective of the intended outcome and includes suicide attempts (self-injurious behavior with the intent to die) and nonsuicidal self-injury (NSSI; self-injurious behavior without the intent to die; Hawton et al., 2003 ; Silverman et al., 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 pandemic not only caused damage to individual physical heath, but also have a negative impact on individual mental health (1,2). Recently, a study of 1120 respondents from 194 cities in China showed that 53% respondents reported a moderate or severe psychological impact, and approximately 30.3% (36.4%) respondents reported the symptoms of depression (anxiety) during early COVID-19 outbreak (3).…”
Section: Introductionmentioning
confidence: 99%
“…It is often regarded as a moderator to explain individual differences in susceptibility to mental health problems during the pandemic. On one hand, individuals who use adaptive coping strategy frequently tend to engage in problem solving and take positive measures (e.g., wearing masks for outdoor activities) to protect them from harm in a dangerous world (2,12), which may reduce the impact of stressors on the risk perception of being infected with COVID-19 disease. On the other hand, individuals who use adaptive coping strategy frequently tend to make great effort (e.g., taking medical treatment; receive psychological intervention) in dealing with the potential adverse consequence of being infected with disease (e.g., physical harm) (2), which might reduce the negative effect of the risk perception of being infected with disease on mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, inspired by COVID-19 research done in China (Li et al, 2021), we also explored the relationship between satisfaction with online learning and distress among CISs.…”
Section: The Current Investigationmentioning
confidence: 99%